2017
DOI: 10.5430/jer.v4n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of skin carotenoids as a biomarker of vegetable intake among Mexican-Origin children in a community setting: A cross-sectional pilot study

Abstract: Background and purpose: Studies in adults and children have demonstrated a strong correlation of skin carotenoids with fruit and vegetable (F/V) intake. There are few studies testing the usefulness of this methodology in a community setting. This study aimed to determine the feasibility of resonance Raman spectroscopy (RRS) skin carotenoid intensity scores in young children to assess F/V intake. Methods: A cross-sectional study design was used to capture the RRS skin carotenoid intensity scores using the Pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The small sample size and large variation in Veggie Meter ® scores likely made it difficult to estimate effect size. To date, though, there has been limited published research on using Veggie Meter ® with Latino children or adults [ 47 , 48 ] and few studies have assessed skin carotenoids among Latino/a children [ 49 , 50 ]. However, based on the authors’ knowledge, there have been no published studies using the Veggie Meter ® with Latino/a children living in border communities and only one study that obtained Veggie Meter ® scans at more than one time point for a subsample of Latino/a children [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The small sample size and large variation in Veggie Meter ® scores likely made it difficult to estimate effect size. To date, though, there has been limited published research on using Veggie Meter ® with Latino children or adults [ 47 , 48 ] and few studies have assessed skin carotenoids among Latino/a children [ 49 , 50 ]. However, based on the authors’ knowledge, there have been no published studies using the Veggie Meter ® with Latino/a children living in border communities and only one study that obtained Veggie Meter ® scans at more than one time point for a subsample of Latino/a children [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting measurement is a score ranging from 0 to 70 000 and above. Studies have demonstrated positive correlation between skin carotenoid levels and fruit and vegetable consumption in adults and children (24)(25)(26) . In Mexican-origin children, measurement of skin carotenoids is correlated with dietary intake of vegetables (r = 0•41, P = 0•03, n 51) (25) .…”
Section: Outcome Measure and Other Variablesmentioning
confidence: 99%
“…Studies have demonstrated positive correlation between skin carotenoid levels and fruit and vegetable consumption in adults and children (24)(25)(26) . In Mexican-origin children, measurement of skin carotenoids is correlated with dietary intake of vegetables (r = 0•41, P = 0•03, n 51) (25) . Also, changes in skin carotenoids closely follow plasma carotenoid changes, as shown in a controlled feeding trial providing a broad range of carotenoid intakes (26) .…”
Section: Outcome Measure and Other Variablesmentioning
confidence: 99%